History, Memory and Migration - Glynn, Irial. author. aut Link
XIV, 251 p.
Keywords: By conversing with the main bodies of relevant literature from Migration Studies and Memory Studies, this overview highlights how analysing memories can contribute to a better understanding of the complexities of migrant incorporation. The chapters consider international case studies from Europe, North America, Australia, Asia and the Middle East.